Toxic effects of Sapium baccatum (Ludai) extract in rats (Kesan toksik ekstrak Sapium baccatum (Ludai) ke atas tikus) - Bakhtiar, M. Taher; Mat Alewi, Nur Aizura; Darnis, Deny Susanti; Zamli, Zaitunnatakhin; Ramli, Norazsida; Saad, Nurulwahida (Penerbit UKM, 2012)
Sapium baccatum is usually used as a timber. Its medicinal values are not well known and very little research has been conducted concerning the plant. Consequently, this study was conducted to observe toxicity effects of hexane extract of stem bark of S. baccatum. The toxicity effects were assessed through observation of physiological changes of the rats as well as through gross and histological examinations of its livers. The doses for the treated groups were given intraperitoneally for T2, T3 and T4 group which were given 100, 250 and 500 mg/kg, respectively. Meanwhile, control group (T1) was administered with 80 % PEG 200 only. The observation period was 14 days. If the rat died, it was dissected and the liver was removed and examined. Some physiological effects observed include ataxia and hind-legs paralysis. The gross observations of the livers, growth of abnormal spots and connective tissues attachment to lobes of the livers were observed. The experiment was followed by histopathological observation, which indicated the presence of abnormal hepatocytes with a distorted shape and undefined cell linings for T2 group. Results also indicated an increase in the distortion of hepatocytes, presence of massive cytoplasm and necrosis of hepatocytes for T3 and T4 groups. Therefore, results suggest that non polar extract of the stem bark of S. baccatum may promote toxic effects to the animals.